ANALISIS KERJA SAMA INDONESIA-JEPANG DALAM PENINGKATAN KUALITAS DAN KAPASITAS SUMBER DAYA MANUSIA INDONESIA TAHUN 2020-2021 - Hardi Alunaza; Fernandez (Jurnal Ilmiah Hubungan Internasional Fajar, 2023)
This paper will explain the cooperation carried out by Indonesia and Japan in improving the quality of Indonesian human resources. The cooperation was carried out by Indonesia as an effort to face the disruption and transformation of massive industry 4.0 which demands rapid development in the industrial sector. Indonesia, which indexes has the quality and competitiveness of human resources, will certainly overcome these problems, one of which is through cooperation with Japan. Japan, which incidentally is a developed country in the industrial sector, certainly has the quality and capability of good and compatible human resources. In analyzing the cooperation between Indonesia and Japan, the author uses the international cooperation and dual economy perspective. This paper uses qualitative with descriptive research method and library research of data collection. The result of this research reveals that there are three collaborations carried out by Indonesia and Japan in improving the quality of human resources namely Indonesia Japan 2045, Indonesia Japan Business Network, and Training for Trainers LEMMI 4.0. These three things are Indonesia’s strategy to be able to compete and improve the quality of human resource.